Developing a New Strategy for Delivery of Neural Transplant Populations Using Precursor Cell Sprays and Specialized Cell Media. Issue 9 (11th July 2021) - Woods, William A.; Chowdhury, Farhana; Tzerakis, Nikolaos; Adams, Christopher F.; Chari, Divya M.
Abstract : Neural precursor/stem cell transplantation therapies promote regeneration in neurological injuries, but current cell delivery methods have drawbacks. These include risks with surgical microinjection (e.g., hemorrhage, embolism) and high cell loss with systemic delivery/passage through fine gauge needles. Aerosolized cell delivery offers significant benefits including rapid and minimally invasive cell delivery, and ease of delivery to end users. To develop this approach, it is necessary to prove that 1) aerosolization does not have detrimental effects on transplant cells and 2) suitable media can be identified to support cell delivery. To achieve these aims, cells are sprayed using a commercial spray device or stored in Hibernate‐A, a CO2 ‐independent nutrient solution. Histological assessments consist of cell viability analysis, immunocytochemistry, and EdU labeling. It is shown that a major neural precursor transplant population—oligodendrocyte precursor cells (OPCs)—survive following aerosolized delivery and retain their capacity for proliferation and differentiation (key to their repair function). Hibernate‐A can support OPCs' survival without specialized maintenance conditions, with no detrimental impact on cell fate. It is considered that this data supports the concept of a novel class of advanced medical spray devices to facilitate transport and delivery of transplant populations in neural cell therapy. Abstract : First report showing that the transplant population of oligodendrocyte progenitor cells (OPCs) can survive aerosolized delivery, and can also survive in a CO2 independent nutrient solution without specialized maintenance conditions. Cells retain important regenerative features after spraying or storage in nutrient solution. The data support the feasibility of developing regenerative medical cell spray devices for neural cell transplantation therapy.